Antimicrobial and Antioxidant Activities and Phenolic Profile of Eucalyptus globulus Labill. and Corymbia ficifolia (F. Muell.) K.D. Hill & L.A.S. Johnson Leaves - Ștefan Dezsi; Alexandru Sabin Bădărău; Cristina Bischin; Dan Cristian Vodnar; Radu Silaghi-Dumitrescu; Ana-Maria Gheldiu; Andrei Mocan; Laurian Vlase (Molecules, 2015)
This study was performed to evaluate the in vitro antimicrobial and antioxidant activities and the phenolic profile of Eucalytus globulus Labill. and Corymbia ficifolia (F. Muell.) K.D. Hill & L.A.S. Johnson leaves. Both leave extracts contain significant amounts of phenolic compounds, mainly flavonoids. Qualitative and quantitative analyses of the phenolic compounds were performed using a HPLC/MS method. The main flavonoid was hyperoside and its highest amount was found in E. globulus (666.42 ± 5.02 μg/g dw plant material). Regarding the flavonol profile, myricetin was the dominant compound and its highest amount was found in C. ficifolia leaves (124.46 ± 0.24 μg/g dw plant material). The antioxidant activity was evaluated by DPPH, TEAC, hemoglobin ascorbate peroxidase activity inhibition (HAPX) and inhibition of lipid peroxidation catalyzed by cytochrome c assays, revealing an important antioxidant potential for both species. In the antimicrobial assays, C. ficifolia extract was found to be more active than E. globulus against both Gram-positive and Gram-negative bacterial strains with the exception of Bacillus subtilis. The results of the present study provide new valuable data regarding the bioactivities of these medicinal species.